ANALISIS BRAND IMAGE TERHADAP MADRASAH TSANAWIYAH PADA YAYASAN NURUL ISLAM DI LAMPUNG SELATAN - -, Aswin; Masturi, Hafiz (Jurnal Manajemen dan Keuangan, 2010)
Now days, Industry of telecomunication celluler offered various facilities such as service quality as well as good presentation to give plus value at the service that offered so will create satisfied at the consumer it self which result the loyality at the consumer it self.Service quality, satisfaction and brand loyality at consumer it self in comparison through four service dimensions is reliable dimension, responsive dimension, emphaty dimension and assurance dimension with that methods use average test is Serqual method with test technique wilcoxonmath test, regresion analys, clasical asumtion test and normalitas test.Relation among service quality, consumer satisfaction and brand loyality for company will give deeply effect for market later on.Keyword : service dimension, service quality, consumers satisfaction, brand loyality